(untitled) (Latakia University Journal -Biological Sciences Series, 2018)
This research was conducted in plastic house in Zahed local for organic agriculture in Tartous in two agriculture season during(2014-2015) and(2015-2016) to study the effect of fermentation fertilizers and different amount of liquid organic fertilizer from digstate on number of flower cluster, number of flowers, fruit set%, and production quantity of tomato plant in green house by using 10 fertilizer treatments. The results of research showed that: all treatments of organic fertilizers and farmer treatment was significantly superior to witness treatment (without fertilizer) on number of flower cluster, number of flowers , fruit set%, early production and all production/plant and yield, the results showed as well as significant increase in all characteristics with increasing liquid organic fertilizer from dig state amount. نفّذ هذا البحث في بيت بلاستيكي في موقع زاهد للزراعات العضوية في طرطوس لموسمين زراعيين متتاليين (2014-2015) و(2015- 2016)، وتمّ فيه دراسة تأثير إضافة الأسمدة العضوية المتخمرة وكميات مختلفة من الأسمدة العضوية السائلة الناتجة عن التخمر اللاهوائي في عدد العناقيد الزهرية، والأزهار على النبات ونسبة العقد، وكمية إنتاج البندورة تحت ظروف الزراعة المحمية، شمل البحث 10 معاملات تسميد. بينت النتائج تفوق كافة معاملات التسميد العضوي ومعاملة المزارع وبفروق معنوية واضحة على معاملة الشاهد(بدون تسميد) من حيث عدد العناقيد الزهرية وعدد الأزهار/النبات، ونسبة العقد، والإنتاج المبكر والكلي، كما أظهرت النتائج تفوق في كافة الصفات المدروسة مع زيادة كمية الأسمدة العضوية السائلة الناتجة عن التخمر اللاهوائي المضافة.